2013
DOI: 10.1039/c3ra43328e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition synthesis of Al-doped ZnO nanoparticles: an in-depth study

Abstract: Al-doped ZnO nanoparticles are synthesized by means of a heating up solution based thermal decomposition method. The synthesis involves a reaction of zinc acetylacetonate hydrate, aluminium acetylacetonate and 1,2-hexadecanediol in the presence of oleic acid and oleyl amine. A proposed reaction mechanism from reagents to monomers is corroborated by analysis of the evolving gases using headspace GC-MS analysis. The Al-doped ZnO nanoparticles synthesized are dynamically stabilized by adsorbed oleate ions, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…In line with previous studies on CdSe, 28,40 PbS, 41,42 and InP 43 NCs, we have demonstrated that carboxylic acids bind as carboxylates to HfO 2 and ZrO 2 NCs. Using IR spectroscopy, similar conclusions were arrived at for Fe 2 O 3 , 17 MFe 2 O 4 (M = Fe, Mn, and Co), 44 ZnO, 45 and ZrO 2 46 NCs, yet the combination with NMR spectroscopy enables us to complement this finding with the observation that, in the case of HfO 2 and ZrO 2 , the negative charge on the carboxylate moieties is balanced by surface adsorption of protons rather than by excess metal cations. Moreover, carboxylic acids will only bind as carboxylates on the as-synthesized NCs provided that a sufficient amount of oleylamine is supplied, which removes hydrogen chloride initially present at the surface.…”
Section: ■ Discussionsupporting
confidence: 64%
“…In line with previous studies on CdSe, 28,40 PbS, 41,42 and InP 43 NCs, we have demonstrated that carboxylic acids bind as carboxylates to HfO 2 and ZrO 2 NCs. Using IR spectroscopy, similar conclusions were arrived at for Fe 2 O 3 , 17 MFe 2 O 4 (M = Fe, Mn, and Co), 44 ZnO, 45 and ZrO 2 46 NCs, yet the combination with NMR spectroscopy enables us to complement this finding with the observation that, in the case of HfO 2 and ZrO 2 , the negative charge on the carboxylate moieties is balanced by surface adsorption of protons rather than by excess metal cations. Moreover, carboxylic acids will only bind as carboxylates on the as-synthesized NCs provided that a sufficient amount of oleylamine is supplied, which removes hydrogen chloride initially present at the surface.…”
Section: ■ Discussionsupporting
confidence: 64%
“…proposed an analogues C−C cleavage mechanism with the elimination of acetone and ester for the formation of Al‐doped ZnO nanoparticles by the thermal decomposition of the metal acetylacetonates with 1,2‐hexadecanediol. In addition to acetone, thermal decomposition products of ester such as acetic acid, a mixture of alkanes and alkenes, carbon dioxide and water were detected using headspace GC analysis during the synthesis of ZnO:Al nanoparticles …”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…In addition to acetone, thermal decomposition products of ester such as acetic acid, am ixture of alkanes and alkenes, carbon dioxide and water were detected using headspace GC analysis duringt he synthesis of ZnO:Al nanoparticles. [174] Zhang et al developed anonaqueousroute for the synthesis of phase-pure transition metal niobates (InNbO 4 ,M nNb 2 O 6 , and YNbO 4 )b ased on the solvothermalr eactiono fn iobium chloridea nd the corresponding transition metal acetylacetonates in benzyl alcohol. [175] The chemical mechanismsr esponsible for the oxygen supply were based on three almosts imultaneously occurring processes as shown in Scheme 9: a) Am etal promoted alcoholysis of the acetylacetonate ligand leading to the formation of an enolate and benzyl acetate, b) release of acetonet hrough the coordination of benzyla lcohol to the metal center,a nd c) benzyl ether elimination catalyzedb yt he niobium center.…”
Section: Reaction Between Metal Acetylacetonates and Alcoholsmentioning
confidence: 99%
“…Deposition of colloidal TCO NCs as a nanoink is highly appealing for integration into emerging flexible electronics, such as displays, electronic paper, or solar cells [6,7]. While the synthesis of ZnO:Al nanocrystals and films has recently advanced markedly, it still remains a challenge to control dopant incorporation in zinc oxide based TCO NCs [8][9][10][11][12][13][14][15][16]. Even more, probing doping efficiency and understanding whether or not dopants have substituted the desired host atoms are not trivial.…”
Section: Introductionmentioning
confidence: 99%